Effect of Carbon Fiber Nanotubes Tracheotomy Under Swallowing Training Combined with Bronchoscopic Alveolar Lavage: Carbon Fiber Nanotubes Tracheotomy Under Swallowing Training - Li, Fangli; Gong, Fanghua (Cellular and Molecular Biology, 2022)
This study aimed to analyze the effect of carbon fiber nanotube tracheotomy (CFNT) under swallowing training (ST) combined with bronchofiberoscope alveolar lavage (BAL), so as to provide theoretical guidance for the clinical treatment of pulmonary infection. 40 patients with pulmonary infection were selected as the research objects, and the effects of ST combined with BAL were analyzed after CFNT. The patients were randomly divided into four groups: a control group (group A) and three observation groups (groups B, C, and D), with 10 cases in each group. Patients in group A received conventional treatment, patients in group B received conventional treatment + ST, patients in group C received conventional treatment + BAL, and patients in group D received conventional treatment + ST + BAL. The effect of ST + BAL was analyzed after CFNT. The results showed that compared with the group A, the number of lung infections and infection rates in groups C and D was reduced (P < 0.05); the use time and per capita cost of antibiotics in group A were much higher than those in the groups C and D (P < 0.05); and in group B and D, the number of successful extubation of tracheal catheters and the success rate were greatly increased (P < 0.05) and the average time of intubation was dramatically shortened (P < 0.05). The scores of the water swallow test (WST) in groups B and D were much lower than the score of group A (P < 0.05), and the scores for swallowing ability and swallowing dysfunction scores were much different from those of the group A (P < 0.05). In summary, after a CFNT, the lung infection and swallowing function of patients were effectively improved after ST + BAL.